2008
DOI: 10.1111/j.1752-1688.2008.00170.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Volatile Organic Compounds in Aquifers of the United States1

Abstract: Samples of ambient ground water were collected during 1985-2002 from 3,498 wells in 98 aquifer studies throughout the United States. None of the sampled wells were selected because of prior knowledge of nearby contamination. Most of these samples were analyzed for 55 volatile organic compounds (VOCs) to characterize their national occurrence. Volatile organic compounds were found in samples collected from 90 of the 98 aquifer studies. Occurrence frequencies of one or more VOCs for the 98 aquifer studies ranged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 35 publications
(52 reference statements)
0
27
0
Order By: Relevance
“…The water quality criteria and toxicity levels for VOCs are summarized in Rowe et al (1997). Although the concentrations of VOCs in small urban streams are typically well below human or aquatic health standards and guidelines (Bender et al, 2009), effects due to long-term exposure to concentrations below drinking water standards and to mixtures of VOCs are unknown (Carter et al, 2008). VOCs are released into the environment during their production, distribution, storage, handling, and use and can enter both surface water and groundwater supplies from many point and nonpoint sources (Lopes and Bender, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The water quality criteria and toxicity levels for VOCs are summarized in Rowe et al (1997). Although the concentrations of VOCs in small urban streams are typically well below human or aquatic health standards and guidelines (Bender et al, 2009), effects due to long-term exposure to concentrations below drinking water standards and to mixtures of VOCs are unknown (Carter et al, 2008). VOCs are released into the environment during their production, distribution, storage, handling, and use and can enter both surface water and groundwater supplies from many point and nonpoint sources (Lopes and Bender, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Naphthalene is one of polycyclic aromatic hydrocarbons (PAHs), which was commonly detected in China (Guo et al, 2012;Liu and Zhou, 2011;Ma et al, 2014), while seldom detected in the USA (Carter et al, 2008;Moran et al, 2004;Rowe et al, 2007). For many years, naphthalene had been considered as a non-carcinogenic PAH, but in 2000, the US National Toxicology Program revealed clear evidence of the carcinogenic activity of naphthalene in rats (Preuss et al, 2003).…”
Section: Occurrence Assessmentmentioning
confidence: 99%
“…In 2001, VOCs represented 20% of the chemicals with the largest total onsite and offsite releases to the environment. In a 98-aquifer study in the USA, 51% of the well water samples contained one or more VOCs (1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002), assessment level= 0.02 μg/L) [1]. In the same study, researchers found that mixtures of tetrachlorethylene (PCE) and trichloroethylene (TCE) occurred at the greatest number of sites.…”
Section: Introductionmentioning
confidence: 99%